A Contrastive Analysis between English and Batak Toba Language in Prefixes - Sianipar, Herbert Mouren (The Explora, 2022)
Indonesia is one of the big countries in the world consists of many islands which are separated by oceans and islands that has many tribes as well as their languages. One of the tribes in Indonesia is Bataknese. Batak are an ethnic group from North Sumatra. Most of Bataknese are living in North Sumatra. In this contrastive analysis, the writer chooses two languages, first, English as the source language and Batak Toba language as the target language. The writer contrast the form, distribution, function and meaning of those two language and focused on the prfixes. There is correspondence between English and Batak Toba prefixes in terms of form, that is no prefix in Batak Toba can be attached to cluster; There is partly correspondence between English and Batak Toba prefixes in terms of distribution that there is no prefix in English that can be attached to base form of Adverb, either does Batak Toba; There is correspondence between English and Batak Toba prefixes in terms of function; There is partly correspondence between English and Batak Toba prefixes in terms of meaning of both language is not similar in whole. Therefore, in generally, the writer concludes that English and Batak Toba language are partly correspondence in prefixes.